THE PROCESSES OF FUNCTIONAL AND INCOME FARMS POLARISATION IN POLAND IN CONDITIONS OF MARKET ECONOMY - Paszkowski, Stanisław (Acta Scientiarum Polonorum. Oeconomia, 2005)
The paper presents changes in sector of individual farms in Poland under conditions of the market economy. In the population of all farms it is possible to observe dynamic increase of a group of farms without farming activity, and not getting incomes from agricultural production. As a positive result of changes, increase of farms concentrated on agricultural markets and getting incomes from agriculture can be treated. The research confirms deepening of the processes of functional farms’ polarisation into two groups – market-oriented and social ones, what results on farms’ differentiation according to their incomes’ level.